Peningkatan Unit per Man Hour Proses Packing SKU 2 DC pada Line 9 di PT. X - Johana Kezia Davita; Tanti Octavia (Jurnal Titra, 2020)
SKU 2 DC packing process on line 9 PT. X is done manually by operators using three methods. These three methods were analyzed with time study and simulated with Promodel software. Methods with higher unit per man hour which are method 1 with seven operators and method 2 with eight operators are analyzed again and given some improvements. Operators improve their motion based on two hands process chart, focusing the work of the operator by fixing the job description, improve the working space layout, and change the speed of wrapping machine. There are two solution improvements. Solution 1 is using method 1 with 88 ppm wrapping machine speed and solution 2 is using method 2 with 120 ppm wrapping machine speed. The result of the improvements is an increase in productivity of 3,85% for solution 1 to 13,46 unit per man hour and 15,3% for solution 2 to 16,05 unit per man hour.